Atmospheric Ice‐Nucleating Particles in the Dusty Tropical Atlantic. Issue 4 (18th February 2018) - Price, H. C.; Baustian, K. J.; McQuaid, J. B.; Blyth, A.; Bower, K. N.; Choularton, T.; Cotton, R. J.; Cui, Z.; Field, P. R.; Gallagher, M.; Hawker, R.; Merrington, A.; et al.
Abstract: Desert dust is one of the most important atmospheric ice‐nucleating aerosol species around the globe. However, there have been very few measurements of ice‐nucleating particle (INP) concentrations in dusty air close to desert sources. In this study we report the concentration of INPs in dust laden air over the tropical Atlantic within a few days' transport of one of the world's most important atmospheric sources of desert dust, the Sahara. These measurements were performed as part of the Ice in Clouds Experiment‐Dust campaign based in Cape Verde, during August 2015. INP concentrations active in the immersion mode, determined using a droplet‐on‐filter technique, ranged from around 10 2 m −3 at −12°C to around 10 5 m −3 at −23°C. There is about 2 orders of magnitude variability in INP concentration for a particular temperature, which is determined largely by the variability in atmospheric dust loading. These measurements were made at altitudes from 30 to 3, 500 m in air containing a range of dust loadings. The ice active site density ( n s ) for desert dust dominated aerosol derived from our measurements agrees with several laboratory‐based parameterizations for ice nucleation by desert dust within 1 to 2 orders of magnitude. The small variability in n s values determined from our measurements (within about 1 order of magnitude) is striking given that the back trajectory analysis suggests that the sources of dust were geographically diverse. This is consistent with previous work, which indicates that desert dust's ice‐nucleating activity is only weakly dependent on source. Key Points: For the first time, we measured ice‐nucleating particle concentrations in the dusty eastern tropical Atlantic from an aircraft Ice‐nucleating particle concentrations ranged from 10 2 m −3 at −12°C to around 10 5 m −3 at −23°C Derived ice active site densities were within 1 to 2 orders of magnitude of laboratory‐based parameterizations depending on temperature